Neural Correlates of Recognition Memory in Children with Febrile Seizures: Evidence from Functional Magnetic Resonance Imaging - Kipp, Kerstin H.; Opitz, Bertram; Becker, Martina; Hofmann, Juliane; Krick, Christoph; Gortner, Ludwig; Mecklinger, Axel (Frontiers in Human Neuroscience, 2012)
Febrile seizures (FS) are assumed to not have adverse long-term effects on cognitive development. Nevertheless, FS are often associated with hippocampal sclerosis which can imply episodic memory deficits. This interrelation has hardly been studied so far. In the current study 13 children who had suffered from FS during infancy and 14 control children (7–9 years old) were examined for episodic and semantic memory with standardized neuropsychological tests. Furthermore, using functional magnetic resonance imaging (fMRI) we studied neuronal activation while the children performed a continuous recognition memory task. The analysis of the behavioral data of the neuropsychological tests and the recognition memory experiment did not reveal any between group differences in memory performance. Consistent with other studies fMRI revealed repetition enhancement effects for both groups in a variety of brain regions (e.g. right middle frontal gyrus, left parahippocampal gyrus) and a repetition suppression effect in the right superior temporal gyrus. Different neural activation patterns between both groups were obtained selectively within the right supramarginal gyrus (BA 40). In the control group correct rejections of new items (CR) were associated with stronger activation than correctly identified old items (HITs) whereas in the FS group no difference occurred. On the background that the right supramarginal gyrus is assumed to mediate a top-down process to internally direct attention towards recollected information, the results could indicate that control children used strategic recollection in order to reject new items (recall-to-reject). In contrast, the missing effect in the FS group could reflect a lack of strategy use, possibly due to impaired recollective processing. This study demonstrates that FS, even with mainly benign courses, can be accompanied by selective modifications in the neural memory network.